2018
DOI: 10.1200/edbk_200939
|View full text |Cite
|
Sign up to set email alerts
|

Global Epidemiology, Prevention, and Management of Hepatocellular Carcinoma

Abstract: The incidence rate of hepatocellular carcinoma (HCC) is rising. It is one of the most common cancers worldwide and accounts for substantial morbidity and mortality. Chronic hepatitis B virus (HBV) infection, chronic hepatitis C virus (HCV) infection, and nonalcoholic fatty liver disease (NAFLD) are the most important etiologies of HCC, and effective screening and management strategies are crucial to reduce the HCC risk. For HBV, which accounts for the majority of HCC cases, most infections were acquired via pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(158 citation statements)
references
References 160 publications
3
152
0
3
Order By: Relevance
“…Recently, the development of therapies and methods for controlling hepatitis B virus and hepatitis C virus infections has led to a reduction in the mortality rate of viral HCC worldwide . On the other hand, the incidence of NASH, the aggressive inflammatory form of nonalcoholic fatty liver disease (NAFLD) without viral etiology, and NASH‐associated cirrhosis and HCC is rapidly increasing . Moreover, molecular‐based therapies for NASH have been developed, and these therapies could also help us understand the progression mechanisms of NASH and NASH‐associated HCC.…”
Section: Gut Microbiota and Nashmentioning
confidence: 99%
“…Recently, the development of therapies and methods for controlling hepatitis B virus and hepatitis C virus infections has led to a reduction in the mortality rate of viral HCC worldwide . On the other hand, the incidence of NASH, the aggressive inflammatory form of nonalcoholic fatty liver disease (NAFLD) without viral etiology, and NASH‐associated cirrhosis and HCC is rapidly increasing . Moreover, molecular‐based therapies for NASH have been developed, and these therapies could also help us understand the progression mechanisms of NASH and NASH‐associated HCC.…”
Section: Gut Microbiota and Nashmentioning
confidence: 99%
“…At the same time, the incidence of virus‐related liver disease has been decreasing thanks to vaccination against hepatitis B virus (HBV) and direct‐acting antiviral therapies for HCV. As a result, the etiology of HCC has been changing: although the proportion of HCCs caused by chronic viral hepatitis is still higher than that caused by NAFLD, chronic viral hepatitis is becoming less common as a cause of HCC, whereas NAFLD is becoming more common, especially in the developed countries . Consequently, the assessment of liver fibrosis is increasingly important for patients with NAFLD.…”
Section: Assessment Of Liver Fibrosismentioning
confidence: 99%
“…As a result, the etiology of HCC has been changing: although the proportion of HCCs caused by chronic viral hepatitis is still higher than that caused by NAFLD, chronic viral hepatitis is becoming less common as a cause of HCC, whereas NAFLD is becoming more common, especially in the developed countries. 21 Consequently, the assessment of liver fibrosis is increasingly important for patients with NAFLD. Evaluation of the fibrosis stage is also important in NAFLD because most HCC cases in NAFLD occur in patients who also have cirrhosis.…”
Section: Liver Fibrosis In Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…The occurrence of viral hepatitis, cirrhosis, and HCC will continue to decrease with the evolution of antiviral agents. However, the incidence of alcohol and nonalcoholic steatohepatitis is increasing, and many patients show poor residual liver function after diagnosis with HCC …”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence of alcohol and nonalcoholic steatohepatitis is increasing, and many patients show poor residual liver function after diagnosis with HCC. 3 Poor residual liver function is the main negative side effect of liver resection. One randomized control study reported that a wide resection margin is an important prognostic factor.…”
Section: Introductionmentioning
confidence: 99%